Commercial Activity of Intermediary Companies under the Conditions of Market Economy (Economics and region, 2018)
The article deals with the peculiarities of commercial activity of intermediaries in the conditions of a market economy. The author states that all subjects of economic exchange, in one form or another, perform intermediary functions in relation to each other; and agency business is an integral part of market behavior and the objective function of everyone who enters a market exchange. The purpose of the article is to analyze the peculiarities of commercial activity of intermediary companies in the conditions of a market economy. Market exchange in the modern economy is activated by a large number of intermediaries. They create communicative, institutional, regulatory, informational, social and other mechanisms that simplify and accelerate the relationships between sellers and buyers in different sectors of the economy. Commercial intermediation, first and foremost, relates to the trading sector. It is aimed at performing specialized functions in the field of wholesale and retail trade. The article highlights the main features of intermediary activities. It is emphasized that the important characteristic of intermediary activities is its variety. The main types of intermediary activities are described in the following areas: financial intermediation, insurance mediation, information mediation, commercial mediation and mediation in the channels of promotion. It is noted that in a market economy, commercial intermediary activity becomes mature, organizationally, socially and economically separated from other forms of commercial activity. In modern practice the most demanded services of mediation are: information and commerce; commission; scientific advisory (consulting); engineering; leasing; promotional. It is identified in the article the benefits that the company gains through the involvement of an intermediary. As a conclusion, the author states that intermediary activity, on the one hand, is a universal feature of all agents of a market economy. On the other hand, mediation is an independent form of market transactions and exchanges. The activities of intermediaries are an integral part of market relations. It leads to an increase in the productivity of direct producers of goods (services), acceleration of capital turnover, saturation of commodity markets in accordance with the requirements of consumers. Intermediary activity is beneficial both for the customer and for the intermediary, as it allows to distribute goods (services) more efficiently and economically.
Keywords: intermediary; market economy; commercial intermediary activity; market exchange; commodity